2023
DOI: 10.1007/s40279-023-01925-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Sprint Biomechanics in Hamstring Strain Injuries: A Current Opinion on Existing Concepts and Evidence

Christopher Bramah,
Jurdan Mendiguchia,
Thomas Dos’Santos
et al.

Abstract: Hamstring strain injuries are one of the most common injuries in sprint-based sports with the mechanism of injury considered the result of an interaction between applied mechanical strain and the capacity of the muscle to tolerate strain. To date, injury prevention and rehabilitation strategies have frequently focused on enhancing the capacity of the hamstrings to tolerate strain, with little consideration of factors directly influencing mechanical strain. Sprint running biomechanics are one factor proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 98 publications
1
2
0
Order By: Relevance
“…It would result in greater peak MTU length and greater MTU lengthening velocity. An altered hip-knee coordination in this way is generally consistent with others who have noted the potential influence of altered coordination on injury risk 30 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It would result in greater peak MTU length and greater MTU lengthening velocity. An altered hip-knee coordination in this way is generally consistent with others who have noted the potential influence of altered coordination on injury risk 30 .…”
Section: Discussionsupporting
confidence: 89%
“…Previous investigations of hamstring injury mechanisms have primarily considered running at relatively constant and high speeds 25,30 . However, it was recently shown that hamstring injuries often occur when athletes are accelerating 31 and not necessarily at high running speeds 22 .…”
Section: Introductionmentioning
confidence: 99%
“… 22 Second, a literature review was conducted to identify parameters with a mechanistic link influencing hamstring tissue stress/strain and/or previous published associations with HSI. 2 This led to an initial draft of the S-MAS, with operational definitions used to visualize parameters based on values published in previous literature detailing maximal velocity sprint running mechanics. 29 , 44 Finally, separate consultations were conducted with practitioners and coaches to establish agreements or disagreements with any of the included parameters and refine operational definitions of the criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, track and field athletes, such as sprinters and jumpers, may benefit from the utilization of eccentric overloading, particularly for the lower limbs. In this context, there is a well-established mechanistic link between running mechanics and hamstring strain ( Bramah et al, 2023 ), which typically occurs during the late-swing phase just before the touch-down, with the biceps femoris long head being the most commonly affected muscle ( Zabaloy et al, 2023 ). Therefore, achieving long-term increases in capacities such as power, sprint-specific endurance, and technique, along with simultaneous enhancements in sprinting performance, requires maximizing adaptations in muscle contractile machinery while minimizing the risk of overreaching, excessive fatigue, and injuries in highly-specialized athletes ( Agudo-Ortega et al, 2023 ; Haugen et al, 2019 ).…”
Section: Isoinertial Trainingmentioning
confidence: 99%